Film & Making Other History: Counterhegemonic Narratives for a Cinema of the Subaltern, by Alejandro Pedregal - David Brancaleone (Alphaville: Journal of Film and Screen Media, 2015)
In an age when postmodernism and idealism, disguised as anti-essentialist metaphysics, have given way to what sociologist Zygmunt Bauman calls “liquid modernity”, a new wave of scholarship is beginning to replace critiques of essence or studies of identity with a renewed interest in social relations. One is reminded of how Marx’s anti-idealist Theses on Feuerbach marked a turn away from contemplation and towards practice, human sensuous activity, and practical-critical praxis which he understood as a revolutionary activity (28).